(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
mThe present study was carried out on 60 patientsm with male factor infertility comparedmwith 60 healthy controls, their ages ranged betweenn20-56 years in Maternity and Childhood Teaching Hilla Hospital and in a biochemistry laboratory of Pharmacy college of Babylon university, between Junem2014 – Junuary 2015. The purpose of this study is to investigate CK activity, serum creatine,mcreatinine levels and semen parametersmin infertile men only ,infertile with DM, smoking ifertile,nand hypertention with infertile patients. The present resultsbshowed a statistically significant deferences (p<0.05) in creatine kinasehactivity, creatine and seminal characteristics while nonmsignificant in creatinine and in Abnormal sperm morphology % . There were statistically significant deferences betweenkthe biochemical and seminal parameters inodiabetes , hypertension and smoking patients and tomcontrol group at a p valuem(P<0.05). There were no observed significantkdifferences in creatinine and Abnormal sperm morphology % of smokerskcompared to control group (P>0.05). The same resultskwere obtained in diabetic and hypertensionkwhen compared tojcontrol group (P<0.05). Our resultsjindicated that thejdiabetes , hypertension and smoking reducelserum CK creatinine and semen parameters inkmale infertility . Enzymetic activity of CK inkserum is a biochemical marker in determining infertility and this biochemicalkmarker will represents an important diagnostic feature withmseminal parameters in the future.